Development of wireless and intelligent home automation system - Khalil Azha Mohd Annuar; Muhammad Faiq Maharam; Nik Azran Ab Hadi; Mohamad Haniff Harun; Mohd Firdaus Mohd Ab Halim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The Intelligent Home Automation System (IHAS) is usually a cell phone web-based application that enables end users in order to keep track of in addition to manage home/office appliance using their mobile system. The main objective of this system is developed to facilitate home users, especially domestic electrical appliances with simple controls. In addition, it can save the cost of electricity for lighting can be controlled to suit the user. Generally, most home appliances controlled from a distance using a remote control. Has created a system for controlling home lighting from a certain distance, which replaces the remote control using mobile smartphone. To make the smartphone to function as a remote control, an application was developed using Android technology. App Inventor software used for designing applications intended. Hardware microcontroller Arduino UNO R3 which is used to connect the smartphone to the electrical equipment. The system has been tested by developing a mini model and take into account the situation in the domestic home. The test is based on the level of control for wirelessly using Bluetooth and the distance between the lamp and the smartphone. The results of this test, the system can be used on equipment or other home appliances for the purpose of controlling or adjustment. In addition, the security system was also highlighted in a typical system, using the global system for mobile (GSM), it can be warned and notified to the consumer where there is a gas leak or the presence of a person in the vicinity of the residence.